Interactive 3D Segmentation of Lymphatic Valves in Confocal Microscopic Images - Jonathan-lee Jones (Image Analysis and Recognition, 2016)
We present a novel method of segmentation of lymph valve leaflets from confocal microscopy studies. By using a user informed, layer based segmentation framework, we segment the outer boundary of the lymph valve in 3D from a series of confocal images. This boundary is then used to compute the surface structure of the vessel by providing a boundary constraint to a dual graph based on minimum surface segmentation. This segmentation creates a point cloud of voxels on the surface of the valve structure, we then apply an RBF interpolation to reconstruct it as a continuous surface.